2006
DOI: 10.1007/s11294-006-6133-z
|View full text |Cite
|
Sign up to set email alerts
|

Power Politics and International Labor Standards

Abstract: This paper analyzes how a country's commitment to labor standards is affected by the international political power they possess. Powerful countries may be less committed to actual enforcement of certain labor standards since they are unlikely to face significant threats of international sanctions regardless of their actions. The paper introduces an index of international power for 116 countries that is used to examine how power affects the extent to which countries enforce standards relating to freedom of asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…In particular, I bring evidence that promoting some of the ILO core labor standards such as freedom of association, collective bargaining, right to organize, and safety conditions in the workplace, has a significant and positive impact on export performance. These results are in line with previous studies that have shown, among other things, that higher labor standards generate productivity gains, raise competitiveness, and improve trade relations between countries (Rodrik 1996;Martin and Maskus 2001;Kucera 2002;Deloach et al 2006). Higher levels of labor standards do "help the development process" of Nations as stated in the ILO's Constitution (ILO 2003) and therefore should be promoted.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, I bring evidence that promoting some of the ILO core labor standards such as freedom of association, collective bargaining, right to organize, and safety conditions in the workplace, has a significant and positive impact on export performance. These results are in line with previous studies that have shown, among other things, that higher labor standards generate productivity gains, raise competitiveness, and improve trade relations between countries (Rodrik 1996;Martin and Maskus 2001;Kucera 2002;Deloach et al 2006). Higher levels of labor standards do "help the development process" of Nations as stated in the ILO's Constitution (ILO 2003) and therefore should be promoted.…”
Section: Resultssupporting
confidence: 90%
“…Economists have shed light on the pros and cons of imposing labor standards. For instance, higher levels of labor standards could generate productivity gains, raise competitiveness, and improve trade relations between countries (Galli 2001;Martin and Maskus 2001;Kucera 2002;Deloach et al 2006). Moreover, some in the developed world object to low standards in poor countries either because they might lead to an "unfair" trading advantage, or out of concern for workers in the developing world.…”
mentioning
confidence: 99%
“…One major econometric concern that needs to be addressed is the endogenous nature of labor standards: labor standards are generally set endogenously, depending on the social, political, and economic development stage of a country (Flanagan, 2003; DeLoach et al, 2006). Therefore, estimation results might not always capture the real impact of labor standards.…”
Section: Empirical Strategy and Model Specificationmentioning
confidence: 99%
“…For instance, higher levels of labor standards could generate productivity gains, raise competitiveness, and improve trade relations between countries (Martin and Maskus, 2001; Kucera, 2002; DeLoach et al, 2006). On the other hand, imposing and administrating the implementation of more rigorous labor standards could raise the costs for firms and increase the prices of goods and services that consumers pay (DeLoach et al, 2006). However, there is no clear agreement on whether labor standards should be imposed on developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation